Breath analysis using FTIR spectroscopy - Andrei A. Bunaciu; Hassan Y. Aboul-Enein (Exploration of Medicine)
Breath analysis is a relatively new topic of study that has a lot of potential for both therapeutic and scientific applications. The volatile organic compounds (VOCs) found in breath are created internally by the body due to environmental interactions, gut and air passage bacteria, and metabolites of ingested precursors. Breath analysis may help diagnose disorders linked to changes in breath composition, according to several recent research. An analytical technique that shows promise for the metabolic examination of breath is infrared spectroscopy. Chemical substances found in exhaled human breath can be used to diagnose illnesses, determine physiological states, or evaluate environmental exposure. Exhaled breath (EB) is the perfect biological fluid because it is nearly limitless and causes little to no discomfort for the patient, which promotes collaboration. Furthermore, EB can be sampled without requiring medical professionals or privacy, and it usually doesn’t produce infectious waste (despite airborne infections), which makes breath analysis a desirable method for a variety of applications. Breath analysis is a non-invasive method that solely uses the volatile composition of the EB to characterize the bloodstream and airways’ volatile content, which indicates the state and condition of the entire body’s metabolism. The absorption strength of the metabolites is still very modest, though, because EB contains minimal amounts of them. Several of the most recent uses of infrared spectroscopy for breath analysis, published between 2020 and 2024, are presented in this study.